2022
DOI: 10.21037/tcr-22-398
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the collagen family members as prognostic markers in clear cell renal cell carcinoma

Abstract: Background: Clear cell renal cell carcinoma (ccRCC) is one of the common malignant tumors worldwide.There is still a lack of effective diagnostic and therapeutic targets for the recurrence and metastasis of ccRCC. In this study, we sought to identify effective diagnostic and therapeutic targets for ccRCC recurrence and metastasis.Methods: Gene Expression Omnibus (GEO) dataset was used to obtain differentially expressed genes (DEGs) between primary and metastasis ccRCC. We used The Cancer Genome Atlas (TCGA), G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Recently, we have shown that, for most cancers, survival prediction can be improved by incorporating clinical and transcriptomic data [20]. Additionally, there is an increasing interest in how ECM-related genes could be used to assess the survival of ccRCC patients [21][22][23][24]. To the best of our knowledge, COL7A1 expression in ccRCC was not investigated as an independent prognostic biomarker in this disease, and this is the first ccRCC study using five independent public datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown that, for most cancers, survival prediction can be improved by incorporating clinical and transcriptomic data [20]. Additionally, there is an increasing interest in how ECM-related genes could be used to assess the survival of ccRCC patients [21][22][23][24]. To the best of our knowledge, COL7A1 expression in ccRCC was not investigated as an independent prognostic biomarker in this disease, and this is the first ccRCC study using five independent public datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown that, for most cancers, survival prediction can be improved by incorporating clinical and transcriptomic data [17]. Additionally, there is an increasing interest in how ECM-related genes could be used to assess the survival of ccRCC patients [18][19][20][21]. To the best of our knowledge, COL7A1 expression in ccRCC was not investigated as an independent prognostic biomarker in this disease.…”
Section: Introductionmentioning
confidence: 99%